Chapter 1 Technical and further education after COVID New opportunities or new inequalities? - Esmond, Bill (Taylor & Francis, 2022)
Technical and vocational education have assumed a significant role in the plans of developed nations to overcome economic crisis, relocating learning into the workplace and extending it to higher levels. Policy discourses are based on the premise that education polarised between universities and low attainment has poorly served the needs of modern economies and young people. This chapter sets out the principal claims of these approaches to improve youth transitions and contribute to social justice. These claims are traced back to their origins in the shift to service-based economies and collapse of youth labour markets, leading to a crisis in vocational education and fuelling demand for higher education credentials; and to the emergence of international policies aiming to reconstitute youth transitions on neoliberal lines. Addressing these questions from a social justice perspective, we ask whether such disruption of the educational divide between general and vocational routes has eroded its role in reproducing and validating the social structures of the post-war period, with the creation of new routes and the postulation of new elites validating the emergence of existing and new forms of educational and social inequity.